Emergent 1/3 magnetization plateaus in pyroxene CoGeO_{3} - H. Guo; L. Zhao; M. Baenitz; X. Fabrèges; A. Gukasov; A. Melendez Sans; D. I. Khomskii; L. H. Tjeng; A. C. Komarek (Physical Review Research, 2021)
Despite the absence of an apparent triangular pattern in the crystal structure, we observe unusually well-pronounced 1/3 magnetization plateaus in the quasi-one-dimensional Ising spin chain compound CoGeO_{3} which belongs to the class of pyroxene minerals. We succeeded in uncovering the detailed microscopic spin structure of the 1/3 magnetization plateau phase by means of neutron diffraction. We observed changes of the initial antiferromagnetic zero-field spin structure that resemble a regular formation of antiferromagnetic “domain wall boundaries,” resulting in a kind of modulated magnetic structure with a 1/3-integer propagation vector. The net ferromagnetic moment emerges at these “domain walls” whereas two thirds of all antiferromagnetic chain alignments can be still preserved. We propose a microscopic model on the basis of an anisotropic frustrated square lattice to explain the observations.